2017
DOI: 10.1038/aps.2016.132x
|View full text |Cite|
|
Sign up to set email alerts
|

The lncRNA XIST exhibits oncogenic properties via regulation of miR-449a and Bcl-2 in human non-small cell lung cancer

Abstract: Long non-coding RNAs (lncRNAs) are associated with the occurrence, development and prognoses of non-small cell lung cancer (NSCLC). In the present study, we investigated the functional mechanisms of the lncRNA XIST in two human NSCLC cell lines, A549 and NCI-H1299. In all the 5 NSCLC cell lines (NL9980, NCI-H1299, NCI-H460, SPC-A-1 and A549) tested, the expression levels of XIST were significantly elevated, as compared with those in normal human bronchial epithelial cell line BEAS-2B. In A549 and NCI-H1299 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In addition, it was also demonstrated that XIST overexpression enhanced the expression and release of pro-inflammatory mediators in microglia. LncRNA XIST has been reported to participate in multiple diseases, including cancer and neurological diseases (16,(23)(24)(25)(26). In spinal cord injury, XIST promoted neuronal apoptosis by regulating AKT phosphorylation (16).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was also demonstrated that XIST overexpression enhanced the expression and release of pro-inflammatory mediators in microglia. LncRNA XIST has been reported to participate in multiple diseases, including cancer and neurological diseases (16,(23)(24)(25)(26). In spinal cord injury, XIST promoted neuronal apoptosis by regulating AKT phosphorylation (16).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of SDF-1/CXCR4 axis upregulates lncRNA Xist in rectal cancer [25]. LncRNA Xist is involved in the intimal metastasis and invasion of NSCLC [26,27]. RT-qPCR demonstrated that CAFs increased the levels of CXCR4 and Xist in A549 or H1299 cells, while silencing SDF-1 in CAFs decreased the expressions of CXCR4 and Xist.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of SDF-1/CXCR4 axis can upregulate lncRNA Xist and participate in the occurrence and development of rectal cancer [25]. LncRNA Xist is involved in the intimal metastasis and invasion of NSCLC [26,27]. Therefore, we speculated whether SDF-1 promotes NSCLC by regulating Xist through CXCR4.…”
Section: Sdf-1 Promotes Lncrna Xist Expression Through Cxcr4mentioning
confidence: 99%
“…They recommended that XIST could be a prognostic factor in NSCLC 141 . Zhang et al identified that XIST has an oncogenic role through controlling of Bcl‐2 and miR‐449a in human NSCLC and XIST upregulation activates cell invasion and metastasis by suppression of miR‐449a 142 …”
Section: Crndementioning
confidence: 99%